Multi-Omic Analysis in a Metabolic Syndrome Porcine Model Implicates Arachidonic Acid Metabolism Disorder as a Risk Factor for Atherosclerosis - Xu, Song-Song; Zhang, Xiu-Ling; Liu, Sha-Sha; Feng, Shu-Tang; Xiang, Guang-Ming; Xu, Chang-Jiang; Fan, Zi-Yao; Xu, Kui; Wang, Nan; Wang, Yue; Che, Jing-Jing; Liu, Zhi-Guo; et al. (Frontiers in Nutrition, 2022)
Background: The diet-induced gut microbiota dysbiosis has been suggested as major risk factor for atherothrombosis, however, the detailed mechanism linking these conditions is yet to be fully understood. Methods: We established a long-term excessive-energy diet-induced metabolic syndrome (MetS) inbred Wuzhishan minipig model, which is characterized by its genetic stability, small size, and human-like physiology. The metabolic parameters, atherosclerotic lesions, gut microbiome, and host transcriptome were analysed. Metabolomics profiling revealed a linkage between gut microbiota and atherothrombosis. Results: We showed that white atheromatous plaque was clearly visible on abdominal aorta in the MetS model. Furthermore, using metagenome and metatranscriptome sequencing, we discovered that long-term excessive energy intake altered the local intestinal microbiota composition and transcriptional profile, which was most dramatically illustrated by the reduced abundance of SCFAs-producing bacteria including Bacteroides, Lachnospiraceae and Ruminococcaceae in the MetS model. Liver and abdominal aorta transcriptomes in the MetS model indicate that the diet-induced gut microbiota dysbiosis activated host chronic inflammatory responses and significantly upregulated the expression of genes related to arachidonic acid-dependent signaling pathways. Notably, metabolomics profiling further revealed an intimate linkage between arachidonic acid metabolism and atherothrombosis in the host-gut microbial metabolism axis.